Peran Dan Tanggung Jawab Dewan Pengawas Syariah (DPS) Terhadap Bank Pembiayaan Rakyat Syariah (BPRS) Dana Sejahtra Yogyakarta - Salihin, Agus (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2020)
The purpose of this study is to discuss how the Role and Responsibilities of the Sharia Supervisory Board (DPS) Against the Syariah Prosperous Bank (SRB) of the Yogyakarta Prosperous Fund. This type of research is field research with a descriptive qualitative approach. The object of research is on the SRB in Yogyakarta. The data collection techniques include observation, interview and documentation. While the data analysis technique, researchers conducted a qualitative analysis by describing the results of field observations, observations and documentation. From the results of the study obtained the answer that the supervision carried out by the Sharia Supervisory Board (DPS) of the Syariah Prosperous Credit Bank (SRB) Yogyakarta Prosperous Fund is not yet fully maximized. In fact, only a small proportion of them have really conducted good supervision. The DPS's awareness of their responsibilities is still not fully realized, which in the end the DPS's participation in the Bank's daily activities cannot be done, even the DPS's arrival to the BPRS to conduct supervision is also very rarely done.